Peran Teacher Support terhadap School Engagement pada Siswa SMA “X” Bandung - Fathia Prihandini; Jane Savitri (Humanitas (Jurnal Psikologi), 2021)
The purpose of this research is to understand the role of teacher’s support in affecting students’ school engagement at SMA “X” Bandung. This research uses quantitative methods with correlation tyoe of research. Participant filled teacher’s support questionnaire based on teacher’s support theory by Skinner & Belmont (1993) and school engagement theory by Fredricks et al (2004). It was found that all three teacher support’s dimension have a significant influence on school engagement (R² = 0,387; p < 0,05) and seen based on teacher support dimension that affecting school engagement are structure (R² = 0,339; p < 0,05), involvement (R² = 0,286; p < 0,05), and autonomy support (R²: 0,272; p: <0,05). Therefore, we can conclude that teacher support has a role on students’ school engagement at SMA “X” Bandung. Keywords: teacher support, school engagement, high school students